PENERAPAN STANDAR AKUNTANSI KEUANGANTANPA AKUNTANBILITAS PUBLIK (SAK ETAP)(KPRI SERBA USAHA MIGAS CEPU) - DARA FEBRY K, ROSITA (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this research is to evaluate implemetation of SAK ETAP about financial statement and explain the differences between the accounting records which is used based SAK ETAP and in KPRI Serba Usaha Migas Cepu. The data research were collected through interview and documentation. The result of research showed the are differences betwee the accounting financial statement in based SAK ETAP with financial statement of KPRI Serba Usaha Migas Cepu.the financial statement KPRI Serba Usaha Migas Cepu consist of balance sheet, income statement, statement changes in equity, cash flow, statement the result of operation and note of financial statement.Keywords : SAK ETAP, financial statement, KPRI Serba Usaha